Comparison of genetic diversity of farmed Oreochromis niloticus and wild unidentified tilapia (Wesafu) using microsatellite markers - ESTHER ADAKU UKENYE; IWALEWA MEGBOWON (Society for Indonesian Biodiversity, 2023)
Abstract. Ukenye EA, Megbowon I. 2023. Comparison of genetic diversity of farmed Oreochromis niloticus and wild unidentified tilapia (Wesafu) using microsatellite markers. Biodiversitas 24: 2953-2957. Nile tilapia (Oreochromis niloticus Linnaeus, 1758) and unidentified tilapia (Wesafu) are cichlid species of important nutritional and economic value with good aquaculture potential. Assessing and comparing the genetic diversity of these cichlid species will assist in information development for conservation and management strategies to improve their overall productivity and sustainable aquaculture production. Using twenty fish specimens each from farmed O. niloticus and ecotype, Wesafu from the wild respectively, we examined the genetic diversity between these two cichlid species. Eight microsatellite loci were utilized to molecularly characterize and compare these two cichlid species from the wild and farm based on their genetic variation levels. Genetic diversity was investigated from isolated, amplified and resolved DNA of the two cichlid species obtained from the wild and farm. The microsatellite markers analysis revealed that ecotype, Wesafu from the wild exhibited higher genetic diversity than farmed O. niloticus as evidenced by the effective number of alleles (1.756), Shannon information index (0.596), observed and expected heterozygosity values (0.682 and 0.400). All genetic diversity indices were observed to have declined in farmed populations due to inbreeding. However, farmed O. niloticus recorded more polymorphism (87%) than ecotype, Wesafu from the wild (75%). Low genetic differentiation was found between the farmed and wild cichlid species according to the fixation index (-0.628) while Principal Coordinate Analysis (PCoA) demonstrated some level of variation between the two cichlid species. This finding provides more insights into the conservation of the genetic resource and better management of these species to minimize inbreeding in aquaculture. We advise that only wild broodstocks should be used for fish restocking in breeding program for sustainable aquaculture production.